Novel Experimental and Clinical Therapeutic Uses of Low-Molecular-Weight Heparin/Protamine Microparticles - Shingo Nakamura; Masanori Fujita; Yasutaka Mori; Hidemi Hattori; Megumi Takikawa; Masayuki Ishihara; Satoko Kishimoto (MDPI AG, 2012)
Low-molecular-weight heparin/protamine microparticles (LMW-H/P MPs) were produced as a carrier for heparin-binding growth factors (GFs) and for various adhesive cells. A mixture of low-molecular-weight heparin (MW: approximately 5000 Da, 6.4 mg/mL) and protamine (MW: approximately 3000 Da, 10 mg/mL) at a ratio of 7:3 (vol:vol) yields a dispersion of microparticles (0.5-3 µm in diameter). LMW-H/P MPs immobilize, control the release and protect the activity of GFs. LMW-H/P MPs can also bind to cell surfaces, causing these cells to interact with the LMW-H/P MPs, inducing cells/MPs-aggregate formation and substantially promoting cellular viability. Furthermore, LMW-H/P MPs can efficiently bind to tissue culture plates and retain the binding of important GFs, such as fibroblast growth factor (FGF)-2. The LMW-H/P MPs-coated matrix with various GFs or cytokines may provide novel biomaterials that can control cellular activity such as growth and differentiation. Thus, LMW-H/P MPs are an excellent carrier for GFs and various cells and are an efficient coating matrix for cell cultures.